Predicting Local Brand Acceptance in the Leather Products Market - Sri Surjani Tjahjawati; Siti Samsiyah Purwaningsih; Sholihati Amalia (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
The purpose of this paper is to analyze the local brand acceptance theoretically and practically and develop an integrated model that explains local brand acceptance in the local leather product market in Indonesia. The data is collected from 297 respondents, namely buyers of local leather brands in Indonesia. Structural Equation Model–Partial Least Square (SEM-PLS) analysis was conducted to analyze the relationship between constructs. Importance-performance map analysis (IPMA) is used to analyze which constructs have the highest level of importance to local brand acceptance and price acceptance. The results show that price acceptance is influenced by product involvement, product knowledge, and prestige sensitivity. Local brand acceptance is only influenced by product involvement and price acceptance. The IPMA results show that product involvement has the highest level of importance to price acceptance. Price acceptance has the highest level of importance to local brand acceptance. This is one of the first studies that predicts local brand acceptance and price acceptance in the local leather product market in Indonesia and clarifies the role of product knowledge, product involvement, prestige sensitivity on their effect on local brand acceptance and price acceptance.